PEMBERDAYAAN MASYARAKAT DESA MARGASARI MENUJU DESA BEBAS KARIES MELALUI PRODUK BERES (BEBAS KARIES) - Setyaningrum, Yunita; Nurhapsari, Arlina; Mayangsari, Regilia Shinta; Yuniar, Savira Nurazky; Indrawati, Silvia Vera; Dimas P. P., Muhammad (Faculty of Dentistry Universitas Islam Sultan Agung, 2023)
Background: The Global Burden of Disease Study 2019 estimates that 3.5 billion people worldwide experience dental and oral health problems, with dental caries being the most common disease. The 2018 RISKESDAS data shows that the greatest caries prevalence is in the 5-year-old (93.4%), 12-year- old (68.8%), 15-year-old (68.1%), 35-44 years (92.1%) and 65 years old. -74 years (95.2%). Dental caries has an impact on the quality of life of the sufferer which can interfere with daily activities so that efforts are needed and people become more aware and care about their oral health. Method: The solution to the problem is carried out by educating the community, one of them are in Margasari, Tegal. Dental Health Education is carried out using poster media to make it more interactive, effective and efficient. Evaluation of the implementation is done by using a questionnaire. The results of the questionnaire were tabulated using SPSS with the Wilcoxon non-parametric test method. Result: wilcoxon signed rank shows that there are 0 negative ranks, 24 positive ranks, and 1 ties. Z value based on negative ranks are -4.322 Conclusion: There is an increase in knowledge of respondents after being given education.